2012
DOI: 10.1155/2012/235840
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Arboreal Ant and Ground-Termite Nests in relation to Their Nesting Sites and Location in a Tropical-Derived Savanna

Abstract: Ecosystem engineers such as ants and termites play an important role in the fertility of tropical soils. Physicochemical analyses were thus carried out on some arboreal ant nests collected from mango (Mangifera indica), bush mango (Irvingia gabonensis), kola (Cola nitida), newbouldia plant (Newbouldia laevis), and oil bean plant (Pentaclethra macrophylla) and on ground nest of termite,Odontotermes sudanensisSjost. (Isoptera: Termitidae) in Nigeria. Arboreal nests, particularly those ofM. indica, were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…The nests and hollow of the trees provided nursery grounds for their development. This work shows that termites on trees are found in mud tubes or nests and this agrees with the works of Ugbomeh et al [17] and Echezona et al [21] who observed arboreal colonies that build nest and tunnels at various heights on trees. The total infestation of 9.8% of the trees in the study area shows that anthropogenic effects may have impacted adversely on termite homes as confirmed by some locals who were interviewed, due to felling of trees for timber, urbanization and development.…”
Section: Fig 5 Termite Mean Caste Percentage Abundance On Tree In Komkomsupporting
confidence: 92%
“…The nests and hollow of the trees provided nursery grounds for their development. This work shows that termites on trees are found in mud tubes or nests and this agrees with the works of Ugbomeh et al [17] and Echezona et al [21] who observed arboreal colonies that build nest and tunnels at various heights on trees. The total infestation of 9.8% of the trees in the study area shows that anthropogenic effects may have impacted adversely on termite homes as confirmed by some locals who were interviewed, due to felling of trees for timber, urbanization and development.…”
Section: Fig 5 Termite Mean Caste Percentage Abundance On Tree In Komkomsupporting
confidence: 92%
“…This means that it is possible to know the termites by their presentations on a particular tree: either as nests or mud tubes. Arboreal nests observed in Persea americana, E. guineensis, C. albidum, Echezona, Igwe, and Attama (2012) to an extent. They observed nests in P. macrophylla and M. indica, but nests were not found on M. indica in this study.…”
Section: Discussionmentioning
confidence: 88%
“…This causes a relative increase in their percentage values in comparison to the surrounding soil in different ecosystems, such as pasture areas, high altitude grasslands, savannah, and tropical forests (DONOVAN et al, 2001;COSARINSKY, 2011;ECHEZONA et al, 2012;SARCINELLI et al, 2013). Clay, when ingested together with the organic matter from soil or litter and mixed with the fecal matter of termites, acts as a cementing material and provides greater cohesion and stability to the structure of termite nests (COSARINSKY, 2011), as well as increased moisture retention capacity and a better microclimate for the organism's activities within the colony (DONOVAN et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the increase in pH, porosity, clay content, organic matter, and nutrients in termite nests, as compared with the surrounding soil that has not been affected by these organisms (ACKERMAN et al, 2007;SARCINELLI et al, 2009;COSARINSKY, 2011;ECHEZONA et al, 2012;SARCINELLI et al, 2013). It is known that the resistant outer layer of the mounds built by Cornitermes cumulans is mainly made of soil, while the central chamber where the colony lives is rich in organic matter (REDFORD, 1984;FERREIRA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation